Thermoplastic resin and method for producing the same, and optical lens comprising the thermoplastic resin

JP2024079821A5Inactive Publication Date: 2024-12-13MITSUBISHI GAS CHEM CO INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024058426
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2018-12-28
Filing Date
2024-04-01
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing optical resins used in lenses lack high refractive index and heat resistance, and there is a demand for materials with improved optical properties to meet the requirements of modern camera lenses.

Method used

A thermoplastic resin is produced using a dicarboxylic acid with specific metals (Li, Na, Mg, Al, K, Ca, Ti, Cr, Fe, Ni, Zn, Sn) in controlled amounts, combined with a diol compound, to enhance refractive index and heat resistance, and optionally incorporating polyester or polyester carbonate structures.

Benefits of technology

The resulting resin exhibits high refractive index (1.650 to 1.720), high heat resistance (glass transition point of 130 to 160°C), and low yellowness index (YI value of 7 to 40), suitable for optical lenses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024079821000001
    Figure 2024079821000001
  • Figure 2024079821000002
    Figure 2024079821000002
  • Figure 2024079821000003
    Figure 2024079821000003
Patent Text Reader

Abstract

To provide a thermoplastic resin having a high refractive index, high heat resistance, and low YI value and a method for producing the same, and an optical lens containing the resin.SOLUTION: The present invention provides a method for producing a thermoplastic resin by reacting a composition comprising a dicarboxylic acid represented by formula (1) and a metal derived from the dicarboxylic acid, wherein the metal contains Li, Na, Mg, Al, K, Ca, Ti, Cr, Fe, Ni, Zn and Sn in the total amount of 10000 ppb or less (R1 and R2 each represent H, a halogen, a C1-6 alkyl group or the like).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermoplastic resin, a method for producing the same, and an optical lens containing the thermoplastic resin. More specifically, the present invention relates to a thermoplastic resin having a high refractive index, high heat resistance, and a low YI value, and an optical lens containing the same. [Background technology]

[0002] Optical glass or optical resin is used as a material for optical lenses used in the optical systems of various cameras such as cameras, film-integrated cameras, video cameras, etc. Optical glass is excellent in heat resistance, transparency, dimensional stability, chemical resistance, etc., but has problems such as high material costs, poor moldability, and low productivity.

[0003] On the other hand, optical lenses made of optical resins have the advantage that they can be mass-produced by injection molding, and polycarbonate, polyester carbonate, polyester resin, etc. are used as high refractive index materials for camera lenses. However, in recent years, the development of resins with high refractive indexes is required due to the trend toward lighter, thinner, shorter, and smaller products. In general, if the refractive index of an optical material is high, a lens element having the same refractive index can be realized with a surface with a smaller curvature, so that the amount of aberration generated by this surface can be reduced, and the number of lenses can be reduced, the polarization sensitivity of the lens can be reduced, and the lens thickness can be reduced to reduce weight.

[0004] When an optical resin is used as an optical lens, in addition to the refractive index and Abbe number, heat resistance, transparency, low water absorption, chemical resistance, low birefringence, and moist heat resistance are required. In particular, in recent years, optical lenses having a high refractive index and high heat resistance are required, and various resins have been developed (Patent Documents 1 to 4), but the current situation is that optical lenses having even better high refractive index and high heat resistance are required. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2018-2893 A [Patent Document 2] JP 2018-2894 A [Patent Document 3] JP 2018-2895 A [Patent Document 4] JP 2018-59074 A Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide a thermoplastic resin having a high refractive index, high heat resistance and a low YI value, a method for producing the same, and an optical lens containing the thermoplastic resin. [Means for solving the problem]

[0007] As a result of extensive research, the inventors have discovered that the above-mentioned problems can be solved by producing a thermoplastic resin using a dicarboxylic acid containing a specific metal in a specific amount, and have arrived at the present invention.

[0008] That is, the present invention is as follows. <1> A method for producing a thermoplastic resin by reacting a composition containing at least a dicarboxylic acid represented by the following formula (1) and a metal derived from the dicarboxylic acid, The method of manufacturing the present invention is characterized in that the metals include Li, Na, Mg, Al, K, Ca, Ti, Cr, Fe, Ni, Zn and Sn in a total amount of 10,000 ppb or less. [ka] (In formula (1), R 1 and R 2each independently represents a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, an alkyl group having 1 to 6 carbon atoms, or an aryl group having 6 to 20 carbon atoms which may contain a heterocyclic atom selected from O, N, and S, an alkenyl group having 2 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or an aralkyl group having 7 to 17 carbon atoms. a and b each independently represent an integer of 0 to 5. <2> The metals include Li, Na, Mg, Al, K, Ca, Ti, Cr, Fe, Ni, Zn, and Sn in a total amount of 54 ppb or more. <1> The manufacturing method is described in the above. <3> The metal contains Fe in an amount of 20 to 3000 ppb. <1> or <2> The manufacturing method is described in the above. <4> The metals include Li in an amount of 1 to 100 ppb, Na in an amount of 2 to 500 ppb, Mg in an amount of 1 to 1000 ppb, Al in an amount of 5 to 500 ppb, K in an amount of 20 to 3000 ppb, Ca in an amount of 5 to 1000 ppb, Ti in an amount of 1 to 100 ppb, Cr in an amount of 5 to 500 ppb, Ni in an amount of 1 to 100 ppb, Zn in an amount of 2 to 100 ppb, and Sn in an amount of 1 to 100 ppb. <1> ~ <3> 1. The method for producing a semiconductor device according to claim 1 , <5> The above method comprises reacting a diol compound represented by the following formula (2) with a composition containing a dicarboxylic acid represented by the formula (1) and a metal derived from the dicarboxylic acid: <1> ~ <4> 1. The method for producing a semiconductor device according to claim 1 , [ka] (In formula (2), R 3 and R 4 each independently represents a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, an alkyl group having 1 to 6 carbon atoms, or an aryl group having 6 to 20 carbon atoms which may contain a heterocyclic atom selected from O, N, and S, an alkenyl group having 2 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or an aralkyl group having 7 to 17 carbon atoms. c and d each independently represent an integer of 0 to 5. <6> The thermoplastic resin is polyester or polyester carbonate. <1> ~ <5> 1. The method for producing a semiconductor device according to claim 1 , <7> A thermoplastic resin comprising a structural unit represented by the following formula (3) and a metal derived from a dicarboxylic acid constituting the structural unit, The metals are Li, Na, Mg, Al, K, Ca, Ti, Cr, Fe, Ni, Zn and Sn in a total amount of 10,000 ppb or less. [ka] (In formula (3), R 5 and R 6 each independently represents a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, an alkyl group having 1 to 6 carbon atoms, or an aryl group having 6 to 20 carbon atoms which may contain a heterocyclic atom selected from O, N, and S, an alkenyl group having 2 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or an aralkyl group having 7 to 17 carbon atoms. e and f each independently represent an integer of 0 to 5. <8> The thermoplastic resin has a YI value of 7 to 40. <7> The thermoplastic resin is as described in the above. <9> the above <7> or <8> An optical lens comprising the thermoplastic resin according to claim 1. Effect of the Invention

[0009] The thermoplastic resin of the present invention has a high refractive index, high heat resistance and a low YI value, and can exhibit excellent effects particularly when used in optical lenses. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 shows the results of NMR measurement of the polyester resin obtained in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will now be described in further detail. The method for producing a thermoplastic resin of the present invention is a method for producing a thermoplastic resin by reacting a composition containing at least a dicarboxylic acid represented by the following formula (1) and a metal derived from the dicarboxylic acid, wherein the metals include Li, Na, Mg, Al, K, Ca, Ti, Cr, Fe, Ni, Zn and Sn in a total amount of 10,000 ppb or less. [ka] In formula (1), R 1 and R 2 each independently represents a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, an alkyl group having 1 to 6 carbon atoms, an aryl group having 6 to 20 carbon atoms which may contain a hetero ring atom selected from O, N, and S, an alkenyl group having 2 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or an aralkyl group having 7 to 17 carbon atoms. 1 and R 2 each independently represents a hydrogen atom, a phenyl group, a naphthyl group, or a substituent selected from the group consisting of the following: [ka] a and b each independently represent an integer of 0 to 5, and preferably each independently represent 0 or 1. Among the compounds represented by formula (1), 2,2'-bis(hydroxycarbonylmethoxy)-1,1'-binaphthyl and compounds represented by the following structural formula are preferred, with 2,2'-bis(hydroxycarbonylmethoxy)-1,1'-binaphthyl being particularly preferred. [ka]

[0012] In the above formula (1), the 1,1'-binaphthyl skeleton improves the heat resistance and refractive index of the thermoplastic resin, and also has the effect of reducing birefringence since it has a conformation in which the bond axis connecting the two naphthalene rings is perpendicular to each other. The binaphthyl skeleton may be any of the R-form, S-form, and racemic form, and is preferably a racemic form. A racemic form that does not require optical resolution has a cost advantage.

[0013] In the present invention, the metal derived from the dicarboxylic acid represented by the formula (1) means a metal component mixed as an impurity during the production of the dicarboxylic acid represented by the formula (1). Examples of such metals include Li, Na, Mg, Al, K, Ca, Ti, Cr, Fe, Ni, Zn, Sn, V, Mn, Co, Cu, Ge, Sr, Zr, Mo, Ag, Cd, Sb, Ba, W, and Pb. Among these, V, Mn, Co, Cu, Ge, Sr, Zr, Mo, Ag, Cd, Sb, Ba, W, and Pb are below the detection limit (<0.005 μg / g), so in the present invention, the total content of Li, Na, Mg, Al, K, Ca, Ti, Cr, Fe, Ni, Zn, and Sn is measured. In the present invention, the metals derived from the dicarboxylic acid represented by the formula (1) contain Li, Na, Mg, Al, K, Ca, Ti, Cr, Fe, Ni, Zn and Sn in a total amount of 10000 ppb or less, more preferably 5870 ppb or less, and particularly preferably 3738 ppb or less. The present inventors have surprisingly found that a thermoplastic resin having a high refractive index, high heat resistance and a low YI value can be obtained by reacting a dicarboxylic acid containing Li, Na, Mg, Al, K, Ca, Ti, Cr, Fe, Ni, Zn and Sn in a total amount of 10000 ppb or less to produce a thermoplastic resin. In the present invention, the metals derived from the dicarboxylic acid represented by formula (1) preferably contain Li, Na, Mg, Al, K, Ca, Ti, Cr, Fe, Ni, Zn and Sn in a total amount of 54 ppb or more.

[0014] In the present invention, the metal derived from the dicarboxylic acid represented by the formula (1) preferably contains Fe in an amount of 20 to 3000 ppb. It is also preferable that Li is contained in an amount of 1 to 100 ppb, Na is contained in an amount of 2 to 500 ppb, Mg is contained in an amount of 1 to 1000 ppb, Al is contained in an amount of 5 to 500 ppb, K is contained in an amount of 20 to 3000 ppb, Ca is contained in an amount of 5 to 1000 ppb, Ti is contained in an amount of 1 to 100 ppb, Cr is contained in an amount of 5 to 500 ppb, Ni is contained in an amount of 1 to 100 ppb, Zn is contained in an amount of 2 to 100 ppb, and Sn is contained in an amount of 1 to 100 ppb. The following Table 1 shows the more preferable content and the particularly preferable upper limit of the content of each metal component.

[0015] [Table 1]

[0016] The thermoplastic resin of the present invention obtained by the above-mentioned production method is a thermoplastic resin containing a structural unit represented by the following formula (3) and a metal derived from a dicarboxylic acid constituting the structural unit, and the metal includes Li, Na, Mg, Al, K, Ca, Ti, Cr, Fe, Ni, Zn and Sn in a total amount of 10,000 ppb or less. [ka] In formula (3), R 5 , R 6 , e and f are R in the formula (1), 1 , R 2 , a and b are synonymous with each other. Specifically, the thermoplastic resin is preferably a polyester resin or a polyester carbonate resin, and in terms of the effects of the present invention, the polyester resin is particularly preferred.

[0017] One of the characteristics of the thermoplastic resin of the present invention is that it has a high refractive index. The refractive index (hereinafter sometimes abbreviated as "nD") at 25°C and a wavelength of 589 nm is preferably 1.650 to 1.720, more preferably 1.660 to 1.710, and even more preferably 1.670 to 1.700. Furthermore, one of the characteristics of the thermoplastic resin of the present invention is high heat resistance, and the glass transition point (hereinafter sometimes abbreviated as "Tg") is preferably 130 to 160°C, and more preferably 140 to 155°C. Moreover, one of the features of the thermoplastic resin of the present invention is that it has a low YI value. Furthermore, the thermoplastic resin of the present invention has a weight average molecular weight (Mw) of preferably 10,000 to 50,000, more preferably 15,000 to 40,000. The weight average molecular weight (Mw) can be measured by the method described in the examples described later.

[0018] The thermoplastic resin of the present invention is not particularly limited as long as it is obtained by reacting a composition containing a dicarboxylic acid represented by the above formula (1) and a metal derived from the dicarboxylic acid, and any diol compound may be used as a raw material. In the present invention, it is preferable to react a diol compound represented by the following formula (2) with a composition containing a dicarboxylic acid represented by the above formula (1) and a metal derived from the dicarboxylic acid. [ka] In formula (2), R 3 and R 4 each independently represents a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, an alkyl group having 1 to 6 carbon atoms, an aryl group having 6 to 20 carbon atoms which may contain a hetero ring atom selected from O, N, and S, an alkenyl group having 2 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or an aralkyl group having 7 to 17 carbon atoms. 3 and R 4 each independently represents a hydrogen atom, a phenyl group, a naphthyl group, or a substituent selected from the group consisting of the following: [ka] c and d each independently represent an integer of 0 to 5, and preferably each independently represent 0 or 1.

[0019] <Other copolymer components> The thermoplastic resin in the present invention has a constitutional unit represented by the above formula (3), preferably a constitutional unit derived from the diol compound represented by the above formula (2), but may also contain a copolymerization component in addition to the above. Examples of the copolymerization component include a dicarboxylic acid component other than that represented by the above formula (1), a diol component other than that represented by the above formula (2), and further a repeating unit having a carbonate bond.

[0020] Specific examples of dicarboxylic acid components as copolymerization components include aliphatic dicarboxylic acid components such as malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, methylmalonic acid, and ethylmalonic acid; monocyclic aromatic dicarboxylic acid components such as phthalic acid, isophthalic acid, and terephthalic acid; polycyclic aromatic dicarboxylic acid components such as 2,7-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,8-naphthalenedicarboxylic acid, anthracenedicarboxylic acid, and phenanthrenedicarboxylic acid; biphenyl dicarboxylic acid components such as 2,2'-biphenyldicarboxylic acid; and alicyclic dicarboxylic acid components such as 1,4-cyclodicarboxylic acid and 2,6-decalindicarboxylic acid. These may be used alone or in combination of two or more. In addition, acid chlorides and esters may be used as derivatives of these. Among these, monocyclic aromatic dicarboxylic acid components, polycyclic aromatic dicarboxylic acid components, and biphenyl dicarboxylic acid components are preferred because they tend to increase heat resistance and refractive index.

[0021] Specific examples of diol components as copolymerization components include aliphatic diol components such as ethylene glycol, propanediol, butanediol, pentanediol, hexanediol, heptanediol, octanediol, and nonanediol; alicyclic diol components such as tricyclo[5.2.1.02,6]decanedimethanol, cyclohexane-1,4-dimethanol, decalin-2,6-dimethanol, norbornane dimethanol, pentacyclopentadecanedimethanol, cyclopentane-1,3-dimethanol, spiroglycol, and isosorbide; hydroquinone, resorcinol, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(3-methyl-4-hydroxyphenyl)propane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, bis(4-hydroxyphenyl)diphenylmethane, and 1,3-bis(2-(4-hydroxyphenyl)-2-propane). Examples of aromatic diol components include bis(4-hydroxyphenyl)benzene, bis(4-hydroxyphenyl)sulfone, bis(4-(2-hydroxyethoxy)phenyl)sulfone, bis(4-hydroxyphenyl)sulfide, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 1,1-bis(4-hydroxyphenyl)cyclohexane, biphenol, 2,2'-bis(2-hydroxyethoxy)-1,1'-binaphthyl, 1,1'-bi-2-naphthol, dihydroxynaphthalene, bis(2-hydroxyethoxy)naphthalene, and 10,10-bis(4-hydroxyphenyl)anthrone. These may be used alone or in combination of two or more. Among these, ethylene glycol and 2,2'-bis(2-hydroxyethoxy)-1,1'-binaphthyl are preferred because they are easy to suppress the decrease in heat resistance and refractive index while improving moldability.

[0022] Specific examples of the repeating unit having a carbonate bond as a copolymerization component include the diol component exemplified by the formula (2) above and the diol component exemplified above as a copolymerization component, which are bonded via a carbonate bond.

[0023] The thermoplastic resin of the present invention may be prepared by subjecting the dicarboxylic acid represented by the above-mentioned formula (1) and a diol compound to an esterification reaction or an ester exchange reaction, and then subjecting the resulting reaction product to a polycondensation reaction to obtain a polymer having a desired molecular weight.

[0024] Specifically, for example, in the presence of an inert gas, a diol component and a dicarboxylic acid component or a diester thereof are mixed and reacted under reduced pressure, usually at 120 to 350° C., preferably at 150 to 300° C. The degree of reduced pressure is changed stepwise, and finally reduced to 0.13 kPa or less to distill off the generated water or alcohols from the system, and the reaction time is usually about 1 to 10 hours.

[0025] As the polymerization catalyst, a known one can be used, and for example, an antimony compound, a titanium compound, a germanium compound, a tin compound, or an aluminum compound is preferable. Examples of such compounds include oxides, acetates, carboxylates, hydrides, alcoholates, halides, carbonates, and sulfates of antimony, titanium, germanium, tin, and aluminum. These compounds can be used in combination of two or more. Among these, tin, titanium, and germanium compounds are preferable from the viewpoint of the melt stability and color of the thermoplastic resin.

[0026] As the transesterification catalyst, a known one can be used, for example, a compound containing manganese, magnesium, titanium, zinc, aluminum, calcium, cobalt, sodium, lithium, or lead element can be used. Specific examples include oxides, acetates, carboxylates, hydrides, alcoholates, halides, carbonates, sulfates, etc. containing these elements. Among these, oxides, acetates, alcoholates, etc. of manganese, magnesium, zinc, titanium, and cobalt are preferred from the viewpoint of the melt stability, color, and small amount of polymer insoluble foreign matter of the thermoplastic resin. Manganese, magnesium, and titanium compounds are more preferred. These compounds can be used in combination of two or more kinds.

[0027] As described above, the thermoplastic resin of the present invention may contain a copolymerization component other than the structural unit represented by the formula (3). For example, in the case of a polyester carbonate resin, in addition to a diol component and a dicarboxylic acid component, a dicarboxylic acid chloride or phosgene may be reacted, or a diol, a dicarboxylic acid, and a biaryl carbonate may be reacted.

[0028] Specific examples of biaryl carbonates include carbonic acid diesters such as diphenyl carbonate, di-p-tolyl carbonate, phenyl-p-tolyl carbonate, di-p-chlorophenyl carbonate, dinaphthyl carbonate, etc. Among these, diphenyl carbonate is preferred.

[0029] The content of the dicarboxylic acid chloride, phosgene, or biaryl carbonate component is preferably less than 42 mol%, more preferably less than 30 mol%, and even more preferably less than 20 mol%, based on 100 mol% of the dicarboxylic acid component.

[0030] <Additives> If necessary, additives such as heat stabilizers, antioxidants, release agents, plasticizers, fillers, and ultraviolet absorbers can be appropriately added to the thermoplastic resin of the present invention and used as a thermoplastic resin composition.

[0031] The release agent is preferably one that is composed of 90% by weight or more of an ester of alcohol and a fatty acid. Specific examples of the ester of alcohol and a fatty acid include an ester of a monohydric alcohol and a fatty acid and / or a partial ester or a full ester of a polyhydric alcohol and a fatty acid. The ester of monohydric alcohol and a fatty acid is preferably an ester of a monohydric alcohol having 1 to 20 carbon atoms and a saturated fatty acid having 10 to 30 carbon atoms. In addition, the partial ester or full ester of a polyhydric alcohol and a fatty acid is preferably a partial ester or a full ester of a polyhydric alcohol having 1 to 25 carbon atoms and a saturated fatty acid having 10 to 30 carbon atoms. Specific examples of the ester of a monohydric alcohol and a saturated fatty acid include stearyl stearate, palmityl palmitate, butyl stearate, methyl laurate, isopropyl palmitate, etc., and stearyl stearate is preferred.

[0032] Specific examples of partial or complete esters of polyhydric alcohols and saturated fatty acids include stearic acid monoglyceride, stearic acid diglyceride, stearic acid triglyceride, stearic acid monosorbitate, behenic acid monoglyceride, pentaerythritol monostearate, pentaerythritol tetrastearate, pentaerythritol tetrapelargonate, propylene glycol monostearate, biphenyl biphenate, sorbitan monostearate, 2-ethylhexyl stearate, dipentaerythritol hexastearate, and other complete or partial esters of dipentaerythritol. Among these esters, stearic acid monoglyceride, stearic acid triglyceride, pentaerythritol tetrastearate, and mixtures of stearic acid triglyceride and stearyl stearate are preferably used.

[0033] The amount of the ester in the release agent is preferably 90% by weight or more, and more preferably 95% by weight or more, when the release agent is taken as 100% by weight. The release agent to be blended in the thermoplastic resin composition is preferably in the range of 0.005 to 2.0 parts by weight, more preferably 0.01 to 0.6 parts by weight, and even more preferably 0.02 to 0.5 parts by weight, per 100 parts by weight of the thermoplastic resin.

[0034] The heat stabilizer includes a phosphorus-based heat stabilizer, a sulfur-based heat stabilizer, and a hindered phenol-based heat stabilizer. Of the phosphorus-based heat stabilizers, preferably tetrakis(2,4-di-tert-butylphenyl)-4,4'-biphenylene diphosphonite is used. The content of the phosphorus-based heat stabilizer in the thermoplastic resin is preferably 0.001 to 0.2 parts by weight based on 100 parts by weight of the thermoplastic resin.

[0035] Of the hindered phenol-based heat stabilizers, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate is particularly preferably used. The content of the hindered phenol-based heat stabilizer in the thermoplastic resin is preferably 0.001 to 0.3 parts by weight based on 100 parts by weight of the thermoplastic resin.

[0036] The ultraviolet absorber is preferably at least one type of ultraviolet absorber selected from the group consisting of benzotriazole-based ultraviolet absorbers, benzophenone-based ultraviolet absorbers, triazine-based ultraviolet absorbers, cyclic iminoester-based ultraviolet absorbers, and cyanoacrylate-based ultraviolet absorbers.

[0037] Benzotriazole-based UV absorbers are more preferably 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole and 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol]. Benzophenone-based UV absorbers include 2-hydroxy-4-n-dodecyloxybenzophenone and 2-hydroxy-4-methoxy-2'-carboxybenzophenone. Triazine-based UV absorbers include 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-[(hexyl)oxy]-phenol and 2-(4,6-bis(2.4-dimethylphenyl)-1,3,5-triazin-2-yl)-5-[(octyl)oxy]-phenol. As the cyclic imino ester type ultraviolet absorbent, 2,2'-p-phenylenebis(3,1-benzoxazin-4-one) is particularly suitable.

[0038] The amount of the ultraviolet absorber to be blended is preferably 0.01 to 3.0 parts by weight per 100 parts by weight of the thermoplastic resin. If the amount is within this range, it is possible to impart sufficient weather resistance to the thermoplastic resin molded product depending on the application.

[0039] <Optical lenses> The thermoplastic resin of the present invention is suitable for optical members, particularly optical lenses. When the optical lens containing the thermoplastic resin of the present invention is manufactured by injection molding, it is preferable to mold it under the conditions of a cylinder temperature of 260 to 350°C and a mold temperature of 90 to 170°C. More preferably, it is preferable to mold it under the conditions of a cylinder temperature of 270 to 320°C and a mold temperature of 100 to 160°C. If the cylinder temperature is higher than 350°C, the thermoplastic resin decomposes and discolors, and if it is lower than 260°C, the melt viscosity is high and molding is likely to be difficult. If the mold temperature is higher than 170°C, it is likely to be difficult to remove the molded piece made of the thermoplastic resin from the mold. On the other hand, if the mold temperature is lower than 90°C, the resin hardens too quickly in the mold during molding, making it difficult to control the shape of the molded piece, or it is likely to be difficult to sufficiently transfer the shape of the molded piece.

[0040] The optical lens of the present invention is preferably implemented as an aspherical lens as necessary. Since an aspherical lens can substantially eliminate spherical aberration with a single lens, it is not necessary to eliminate spherical aberration by combining multiple spherical lenses, and it is possible to reduce weight and molding costs. Therefore, aspherical lenses are particularly useful as camera lenses among optical lenses.

[0041] In addition, the optical lens of the present invention has high molding fluidity and is therefore particularly useful as a material for optical lenses that are thin, small, and have complex shapes. As a specific lens size, the thickness at the center is preferably 0.05 to 3.0 mm, more preferably 0.05 to 2.0 mm, and even more preferably 0.1 to 2.0 mm. In addition, the diameter is preferably 1.0 mm to 20.0 mm, more preferably 1.0 to 10.0 mm, and even more preferably 3.0 to 10.0 mm. In addition, the shape is preferably a meniscus lens with one side convex and the other side concave.

[0042] The optical lens of the present invention can be formed by any method such as metal molding, cutting, polishing, laser processing, electric discharge processing, etching, etc. Among these, metal molding is more preferable in terms of production costs. EXAMPLES

[0043] The present invention will be further described below with reference to examples, but the present invention is not limited to these. The physical properties were measured by the following methods.

[0044] <Metal analysis> After carbonization of the samples with sulfuric acid, the metal concentrations were measured by ICP-MS. That is, 2 g of the sample was weighed into a synthetic quartz beaker, and 2.5 ml of sulfuric acid was added during carbonization and 0.1 ml of sulfuric acid was added before carbonization, while heating and carbonizing on a hot plate. The sample was then covered with a quartz dish and heated in an electric furnace at 500°C for 10 hours to carbonize. Furthermore, sulfuric acid was added and heated to dryness, and nitric acid was added and heated to dryness to perform thermal acid decomposition. A nitric acid solution was added to make 50 mL, and the mixture was heated to 50°C, and quantitative analysis was performed by ICP-MS. ICP-MS equipment: Shimadzu Corporation: ICPE-9000

[0045] <Method of measuring weight average molecular weight (Mw)> The weight average molecular weight in terms of polystyrene was calculated from a calibration curve of a standard polystyrene prepared in advance. That is, a calibration curve was prepared using a standard polystyrene ("PStQuick MP-M" manufactured by Tosoh Corporation) with a known molecular weight (molecular weight distribution = 1), and the elution time and molecular weight value of each peak from the measured standard polystyrene were plotted, and a cubic approximation was performed to obtain a calibration curve. Mw was calculated from the following formula. Mw = Σ(Wi × Mi) ÷ Σ(Wi) Here, i represents the i-th division point when dividing the molecular weight M, Wi represents the i-th weight, and Mi represents the i-th molecular weight. The molecular weight M represents the polystyrene molecular weight value at the same elution time on the calibration curve. The GPC device used was a Tosoh Corporation HLC-8320GPC, with one TSKguardcolumn SuperMPHZ-M as the guard column and three TSKgel SuperMultiporeHZ-M connected in series as the analytical column. Other conditions were as follows. Solvent: HPLC grade tetrahydrofuran Injection volume: 10μL Sample concentration: 0.2 w / v% HPLC grade chloroform solution Solvent flow rate: 0.35ml / min Measurement temperature: 40℃ Detector: RI

[0046] <Measuring method of refractive index (nD, νd)> The obtained resin was press-molded into a 40φ, 3 mm thick disk (molding conditions: 200 °C, 100 kgf / cm 2 , 2 minutes), cut out at a right angle, and the refractive index at a measurement wavelength of 589 nm was measured at 25 °C using a KPR-200 manufactured by Carl Zeiss.

[0047] <Measurement method of YI value> 6 g of the obtained resin was dissolved in 60 ml of methylene chloride, and the YI value was measured based on JIS 7373 using a spectroscopic color difference meter (manufactured by Nippon Denshoku Industries Co., Ltd., trade name "SE-2000") in a cell with an optical path length of 6 cm.

[0048] (Example 1) 50.29 g (0.12 mol) of 2,2'-bis(hydroxycarbonylmethoxy)-1,1'-binaphthyl (hereinafter referred to as "BINOL-DC") represented by the following structural formula, 52.66 g (0.10 mol) of 2,2'-bis(2-hydroxyethoxy)-6,6'-diphenyl-1,1'-binaphthalene (hereinafter referred to as "DP-BHBNA") represented by the following structural formula, 3.49 g (0.06 mol) of ethylene glycol (hereinafter referred to as "EG"), and 0.011 g of tetrabutoxytitanium as a catalyst were placed in a reaction kettle equipped with a stirrer and a distillation apparatus, heated to 180 °C under a nitrogen atmosphere at normal pressure, and stirred for 30 minutes. Thereafter, the polymerization reaction was carried out by raising the temperature to 250 °C and reducing the pressure to 0.13 kPa or less. The content was taken out of the reactor to obtain a polyester resin. As a result of analyzing the obtained polyester resin by NMR, 80 mol% of the diol component introduced into the polyester resin was derived from DP-BHBNA, 20 mol% was derived from EG, and 100 mol% of the carboxylic acid component introduced into the polyester resin was derived from BINOL-DC. The measurement results of NMR are shown in Figure 1. The physical properties of the obtained polyester resin are shown in Table 2.

[0049] [Chemical formula] [Chemical formula]

[0050] Example 2 A polyester resin was obtained in the same manner as in Example 1, except that a different lot of 2,2'-bis(hydroxycarbonylmethoxy)-1,1'-binaphthyl was used. The physical properties of the obtained polyester resin are shown in Table 2. In Table 2, the 2,2'-bis(hydroxycarbonylmethoxy)-1,1'-binaphthyl used in Example 1 is referred to as BINOL-DC-A, and the 2,2'-bis(hydroxycarbonylmethoxy)-1,1'-binaphthyl used in Example 2 is referred to as BINOL-DC-B.

[0051] Example 3 Further, except that a different lot of 2,2'-bis(hydroxycarbonylmethoxy)-1,1'-binaphthyl was used, a polyester resin was obtained in the same manner as in Example 1. The physical properties of the obtained polyester resin are shown in Table 2. In Table 2, the 2,2'-bis(hydroxycarbonylmethoxy)-1,1'-binaphthyl used in Example 3 was referred to as BINOL-DC-C.

[0052] Example 4 50.29g (0.12mol) of 2,2'-bis(hydroxycarbonylmethoxy)-1,1'-binaphthyl (BINOL-DC-A) used in Example 1, 164.41g (0.37mol) of 9,9'-bis(4-(2-hydroxyethoxy)phenyl)fluorene (BPEF) represented by the following structural formula, 55.95g (0.26mol) of diphenyl carbonate, and 0.015g of tetrabutoxytitanium as a catalyst were placed in a reaction vessel equipped with a stirrer and a distillation device, heated to 180°C under normal pressure in a nitrogen atmosphere, and stirred for 30 minutes. Thereafter, the temperature was raised to 255°C and 0.13kPa over 1 hour, the pressure was reduced, and stirring was continued at 255°C and 0.13kPa for 1 hour to carry out a polymerization reaction. The contents were removed from the reactor to obtain a polyester carbonate resin. The physical properties of the obtained polyester carbonate resin are shown in Table 2. [ka]

[0053] (Comparative Example) A polyester resin was obtained in the same manner as in Example 1, except for using 2,2'-bis(hydroxycarbonylmethoxy)-1,1'-binaphthyl containing the metal amount shown in the following Table 2. The physical properties of the obtained polyester resin are shown in Table 2.

[0054] [Table 2] [Industrial Applicability]

[0055] Since the thermoplastic resin of the present invention has a high refractive index, high heat resistance, and a low YI value, it can be used for optical components such as optical disks, transparent conductive substrates, optical cards, sheets, films, optical fibers, lenses, prisms, optical films, substrates, optical filters, and hard coat films, and is particularly useful for camera lenses for smartphones, DSCs, and vehicle-mounted cameras. By using the thermoplastic resin of the present invention, it is possible to reduce the thickness of lens units used for telephoto lenses, etc.

Claims

1. A method for producing a thermoplastic resin by reacting a composition containing at least a dicarboxylic acid represented by the following structural formula and a metal derived from the dicarboxylic acid, The method includes a step of mixing 2,2'-bis(2-hydroxyethoxy)-1,1'-binaphthyl (BHEB) represented by the following structural formula with the composition in the presence of an inert gas, and reacting the mixture at 150 to 300°C using an antimony compound, a titanium compound, a germanium compound, a tin compound, or an aluminum compound as a catalyst, The metals include Li, Na, Mg, Al, K, Ca, Ti, Cr, Fe, Ni, Zn, and Sn in a total amount of 54 to 3738 ppb, and Fe in an amount of 20 to 2000 ppb. 【Chemistry 1】 【Chemistry 2】

2. The method of claim 1, wherein the metals include Li in amounts of 1 to 100 ppb, Na in amounts of 2 to 500 ppb, Mg in amounts of 1 to 1000 ppb, Al in amounts of 5 to 500 ppb, K in amounts of 20 to 3000 ppb, Ca in amounts of 5 to 1000 ppb, Ti in amounts of 1 to 100 ppb, Cr in amounts of 5 to 500 ppb, Ni in amounts of 1 to 100 ppb, Zn in amounts of 2 to 100 ppb, and Sn in amounts of 1 to 100 ppb.

3. A manufacturing method described in claim 1 or 2, wherein the thermoplastic resin is polyester or polyester carbonate.

4. A thermoplastic resin comprising a constitutional unit represented by the following formula, a metal derived from a dicarboxylic acid constituting the constitutional unit, and a constitutional unit derived from 2,2'-bis(2-hydroxyethoxy)-1,1'-binaphthyl (BHEB) represented by the following structural formula: The metals include Li, Na, Mg, Al, K, Ca, Ti, Cr, Fe, Ni, Zn, and Sn in a total amount of 54 to 3738 ppb, and Fe in an amount of 20 to 2000 ppb. 【Chemistry 3】 【Chemistry 4】 5. The thermoplastic resin of claim 4, wherein the thermoplastic resin has a YI value of 7 to 40.

6. An optical lens comprising the thermoplastic resin described in claim 4 or 5.